Morphological changes during the transition from freshwater to sea water in an amphidromous goby, Sicyopterus lagocephalus (Pallas 1770) (Teleostei). Issue 1 (9th October 2014) - Ellien, Céline; Werner, Ugo; Keith, Philippe
Abstract: The widely distributed amphidromous goby Sicyopterus lagocephalus needs drastic change of habitat to fulfil its life cycle: adults live and spawn in rivers, where eggs hatch into prolarvae that have to reach the sea to acquire characteristics of planktonic larvae. Postlarvae return to rivers where they recruit and grow to the adult reproductive stage. Here, we describe the prolarval stages, namely from hatching to first contact with sea water, as well as the first marine larval stages. The observations were made under experimental conditions. We described 3 prolarval substages in freshwater (L1a–L1c). Prolarvae present a slight but visible ontogenetic development in freshwater, during which the yolk sac begins to reduce, the pigmentation increases on the body and in the eyes, and the lenses appear, although the eyes are not functional. Prolarvae need to reach the sea in a maximum of 96 h to pursue their development. Their transfer in sea water at a salinity of 36.5 induces important morphological modifications (i.e. yolk sac full absorption, appearance of pectoral fins, migration of the eyes in anterolateral position of the head, opening of mouth and anus), enabling the organisms to adapt to their new environment. This marine stage is divided into two substages: L2a corresponding to the organisation of the morphological structures adapted to the marine environment and L2b during which these morphological structures become functional. Whether it is in freshwater or sea water, the duration of the substages depends on the water temperature, but is similar for all individuals for a given temperature.